Board Committee Meetings and Firm Financial Performance: An Investigation of Australian Companies1. (25th February 2013) - Hoque, Mohammad Ziaul; Islam, MD. Rabiul; Azam, Mohammad Nurul
Abstract This article examines how the frequency of board committee meetings impacts on Australian firms' financial performance. Data were collected from 118 Australian listed companies – including 26 financial firms and 92 nonfinancial firms – for the period 1999–2007. Analysis of that data shows that the frequencies of audit committee meetings and remuneration committee meetings are positively and significantly associated with return on equity and return on assets. The frequencies of risk committee meetings do not show any significant effects on the financial performance of Australian firms. Estimated results are found to be robust after controlling for internal as well as external governance mechanisms that might affect Australian firm performance.